2008
DOI: 10.1038/nnano.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effect in TiO2 nanoparticles prepared by finely controlled metal assembly on dendrimer templates

Abstract: The use of dendrimer templates to make metal-based nanoparticles of controlled size has attracted much interest. These highly branched macromolecules have well-defined structures that enable them to bind metal ions to generate precursors that can be converted into nanoparticles. We describe the sub-nanometre size control of both anatase and rutile forms of TiO2 particles with phenylazomethine dendrimers, leading to samples with very narrow size distributions. Such fine tuning is possible because both the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
260
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 396 publications
(275 citation statements)
references
References 50 publications
14
260
0
1
Order By: Relevance
“…It is a general understanding that smaller size of transitional metal oxide nanoparticles raises the conduction band and lowers the valence band, and results in the observation of a blue shift in the absorption edge, or we called quantum size effect. On the basis of the study by Saton et al 36 , however, the significant quantum size effect can only be observed for the nanoparticles with diameters o2 nm, in the case of TiO 2 . The commonly used transitional metal oxide nanoparticles usually have diameters much larger than 2 nm.…”
Section: Synthesis and Microscopy Characterizations Of 2d Nanosheetsmentioning
confidence: 96%
“…It is a general understanding that smaller size of transitional metal oxide nanoparticles raises the conduction band and lowers the valence band, and results in the observation of a blue shift in the absorption edge, or we called quantum size effect. On the basis of the study by Saton et al 36 , however, the significant quantum size effect can only be observed for the nanoparticles with diameters o2 nm, in the case of TiO 2 . The commonly used transitional metal oxide nanoparticles usually have diameters much larger than 2 nm.…”
Section: Synthesis and Microscopy Characterizations Of 2d Nanosheetsmentioning
confidence: 96%
“…4 The band 65 structure of TiO 2 with different particle sizes has been studied. 18 The results showed that the particle size on the nanoscale raises the conduction band and lowers the valence band. The widened band gap is displayed as a blue shift of the absorbance edge in UV-Vis absorption spectra.…”
Section: Characterizationmentioning
confidence: 99%
“…More recently Yamamoto and co-workers 28 reported the quantum size effect of small titania clusters prepared by the coordination of Ti acac Cl 3 with poly azomethyne dendrimers. We report herein that individual PAMAM dendrimer molecules can act as a template for titania nanoparticles and that the removal of dendrimer templates by calcinations leads to monodispersed hollow nanoparticles.…”
Section: Introductionmentioning
confidence: 99%